Protective effects of resveratrol on biomarkers of oxidative stress, biochemical and histopathological changes induced by sub-chronic oral glyphosate-based herbicide in rats. Issue 2 (11th January 2019) - Turkmen, Ruhi; Birdane, Yavuz Osman; Demirel, Hasan Huseyin; Kabu, Mustafa; Ince, Sinan
Graphical Abstract: Abstract: The aim of this sub-chronic toxicity study is to determine the protective effects of Resveratrol (Res) on oxidative stress, biochemical and histopathological changes induced by glyphosate-based herbicide (GBH) in the blood, brain, heart, liver and renal tissues. A total of 28 male Wistar rats were equally divided into 4 groups so that each group included 7 rats. In the study, Group I (control group) was given normal rodent feed and tap water ad libitum . Group II (Res group) was given Res 20 mg kg −1, Group III (GBH group) was given GBH of 375 mg kg −1 to achieve 1/10 of Lethal Dose 50% (LD50), and Group IV (Res + GBH) was given Res 20 mg kg −1 and GBH 375 mg kg −1 with oral gavage once a day for 8 weeks. While GBH decreased the glutathione (GSH) levels in the blood, brain, heart, liver and renal tissues, it significantly increased malondialdehyde (MDA) levels. In contrast, the aforementioned parameters were seen to recover in the group to which Res was administered. Moreover, it was observed that Res improved the histopathological changes induced by GBH in rat tissues. In conclusion, Res prevents oxidative stress caused by GBH by preventing lipid peroxidation (LPO) and boosting the antioxidant defense system and decreases the damage in the brain, heart, liver and renal tissues of Wistar rats.